PENGARUH PRESTASI BELAJAR PENDIDIKAN AGAMA ISLAM TERHADAP KARAKTER JUJUR SISWA SMAN 1 TARIK SIDOARJO - Eka Wahyu Hidayati (Universitas Islam Lamongan, 2017)
The learning activities in the subject of Islamic Religious Education is a requirement aimed at building the basic character of students, especially honesty, given the number of students lacking the basic character of honesty in all things either in teaching and learning process or in daily activities. Thus, the writer intends to examine the phenomenon. This study is the result of a field research aimed at answering such problems as firstly the learning achievement of Islamic Religious Education, secondly the character of honesty, thirdly the effect of learning achievement in building the character of honesty, and fourthly the influence of the learning achievement of Islamic Religious Education towards the character of honesty of students in SMA Negeri 1 Sidoarjo. To obtain reliable data, the writer uses such methods as documentation, interview, and questionnaires. In analyzing the data the writer uses the Pearson Product Moment Correlation technique. This study showed that the learning achievement of Islamic Religious Education at SMAN 1 Sidoarjo is classified as moderate, namely 81.4%, while the students classified as having honesty are amounted to 74.3%. The results showed that there was a significant relationship between the learning achievement of Islamic Religious Education and the honesty of students.